The role of skill as a mediator between women’s participation in the informal sector and the subjective economic well-being - Othman, Ab. Razak; Md Jusoh, Zuroni; Abdul Rahim @ Abdul Wahab, Husniyah; Wan Arnidawati, Wan Abdullah (Human Resource Management Academic Research Society, 2022)
This study aims to identify the role of skill as a mediator between women’s participation in the informal sector and subjective economic well-being. Past studies have shown that women’s participation in the informal sector is highly heterogeneous. But the individual encouragement of women to work in the informal sector is made based on individual choice or caused by necessity factors. Informal employment affects women around the world regardless of educational level, income, socio-economic and national development. This employment sector essentially creates many job opportunities and promises to reduce poverty as well as potentially improve the economic well-being of households. However, in reality, the existence of this employment sector, in general, is still vulnerable due to lack of social protection, easy to exploit, outside legal coverage, no employment benefits, low wage scheme, inadequate job security, not covered by insurance, no pension scheme, medical and savings, without sick leave facilities, Employees Provident Fund (EPF) and SOCSO facilities. This study uses a quantitative cross-sectional survey method through a self-administered bilingual questionnaire. A total of 474 respondents among women working in the informal sector in the states of Selangor, Kuala Lumpur, and Putrajaya were involved via stratified random sampling. The data was then analyzed using Statistical Package for the Social Sciences (SPSS) version 24 and IBM AMOS version 23 software. The results showed that there was a significant influence by female participation factor based on necessity (β = 0.251, p <.001) and choice (β = 0.439, p <.001) on skills needs. The results also show that skills act as a mediator in the relationship between women’s participation in the informal sector and subjective economic well-being. These findings indicate that skills are used as a good mediator to test the relationship between women’s participation by necessity and choice for the economic well-being of Malaysian households in the informal sector. Skills can increase productivity and help employees diversify employment opportunities as well as increase their income for the subjective economic well-being of households.